COMPARISON OF WESTERN AND INDONESIAN GESTURES IN COMMUNICATION : SOCIOLINGUISTICS STUDY: SOCIOLINGUISTICS STUDY - Fatin Nadifa Tarigan (Journal of English Education and Linguistics, 2021)
Gestures serve different purposes in language. Nevertheless people find difficulties to learn and to understand the gestures due to the speakers of languages in certain cultures that use “gestures” can change the meaning or the meaning conveyed. This study deals with non-verbal communication strategies named gesture used in Indonesian and Western communication. The objectives of study are to describe the meaning of gestures and to find out the types of gestures used by Indonesian and Western people when communicating in Talk Show. This study applied descriptive qualitative method. The research instrument was video recorder. The data analysis showed that there were 5 types of symbolic movement, 11 types of illustrative movement, 7 types of emotion revealing movement , 3 types of modulation movement, 3 types of adaptable movement. The result of descriptive analysis showed that gestures have big roles in communication either in Indonesian and Western People. Some gestures have similar meaning both of cultures. However sometimes every country has their different meaning of gestures. Therefore, it is necessary to take care before using gestures in other cultures.